LINE-1 DNA methylation: A potential forensic marker for discriminating monozygotic twins. (November 2015) - Xu, Jie; Fu, Guangping; Yan, Lina; Craig, Jeffery M; Zhang, Xiaojing; Fu, Lihong; Ma, Chunling; Li, Shujin; Cong, Bin
Highlights: There are global DNA methylation differences within some healthy concordant monozygotic (MZ) twin pairs. The study developed a quantitative method to analyze the CpG methylation level of LINE-1 using bisulfite pyrosequencing technology to discriminate individules within MZ twins. LINE-1 DNA methylation might be a potential marker for helping to discriminate individual within MZ twins and the discrimination power is 12.61%. More markers can be added to increase the cummulative discrimination power. Abstract: Discriminating individuals within a pair of monozygotic (MZ) twins using genetic markers remains unresolved. This inability causes problems in criminal or paternity cases involving MZ twins as suspects or alleged fathers. Our previous study showed DNA methylation differences in interspersed repeat sequences such as Alu and LINE-1 within pairs of newborn MZ twins. To further evaluate the possible value of LINE-1 DNA methylation for discriminating MZ twins, this study investigated the LINE-1 DNA methylation of a large number of twins. We collected blood samples and buccal cell samples from 119 pairs of MZ and 57 pairs of dizygotic (DZ) twins. Genomic DNA was extracted and LINE-1 methylation level was detected using bisulfite pyrosequencing. The mean methylation level of the three CpG sites in the blood sample among the 176 unrelated individuals was 76.60% and 70.08% in buccal samples. This difference was significant, indicating the tissue specificity of LINE-1 DNA methylation. Among 119 pairs of MZ twins, 15 pairs could be discriminated according to the difference of CpG methylation level between them, which accounted for 12.61% of total number of MZ pairs. As for DZ twins, 10 pairs had significant differences between two individuals, which accounted for 17.54% of the total 57 DZ pairs. In conclusion, there are global DNA methylation differences within some healthy concordant monozygotic (MZ) twin pairs. LINE-1 DNA methylation might be a potential marker for helping to discriminate individuals within MZ twin pairs, and the tissue specificity must be considered in practice.